Oxidative phosphorylation. The specific binding of trimethyltin and triethyltin to rat liver mitochondria - Aldridge, W. N. (1970)
1. The binding of trimethyltin and triethyltin to rat liver mitochondria was determined and the results were analysed by the method of Scatchard (1949). 2. One binding site (site 1) has the correct characteristics for the site to which trimethyltin and triethyltin are attached when they inhibit oxidative phosphorylation. For each compound the concentration of site 1 is 0.8nmol/mg of protein and the ratios of their affinity constants are the same as the ratio of the concentrations inhibiting oxidative phosphorylation. 3. Binding site 1 is present in a fraction derived from mitochondria containing only 15% of the original protein. In this preparation ultrasonication rapidly destroyed site 1. 4. Dimethyltin and diethyltin do not prevent binding of triethyltin to rat liver mitochondria, whereas triethyl-lead does. 5. Trimethyltin and triethyltin bind to mitochondria from brown adipose tissue and the results indicate a binding site 1 similar to that in rat liver mitochondria. 6. The advantages and limitations of this approach to the study of inhibitors are discussed.